Hemiarthroplasty for Femoral Neck Fractures: Does Surgeon Subspecialty Affect Perioperative Outcomes?. Issue 11 (November 2020) - Schumaier, Adam P.; Andrews, Erickson G.; Yue, Ruixian A.; Lake, Samuel S.; Evans, Hardy T.; Scarberry, Nathaniel W.; Kelley, Todd C.; Archdeacon, Michael T.; Le, Theodore T.
Abstract : Objectives: To determine if surgeon subspecialty training affects perioperative outcomes for displaced femoral neck fractures treated with hemiarthroplasty. Design: Retrospective comparative study. Setting: One health system with 2 hospitals (Level I and Level III trauma centers). Patient and Participants: Patients who were treated with hemiarthroplasty for displaced femoral neck fractures between October 2012 and September 2017. Outcome Measures: Leg length discrepancy, femoral offset, estimated blood loss (EBL), incidence of blood transfusion, time to surgery, operative time, and length of stay. Data were analyzed based on the treating surgeon's subspecialty training [arthroplasty (A), trauma (T), other (O)]. Hierarchical regression was used to compare the groups and control for confounding variables. Results: A total of 292 patients who received hemiarthroplasty for displaced femoral neck fractures were included (A = 158; T = 73; O = 61). Surgeon subspecialty had a statistically significant effect on operative time, with arthroplasty surgeons completing the procedure 9.6 minutes faster than trauma surgeons and 17.7 minutes faster than other surgeons ( P < 0.01; ΔR 2 = 0.03). Surgeon subspecialty did not significantly affect other outcomes, including leg length discrepancy ( P = 0.26), femoral offset ( P = 0.37), EBL ( P = 0.10), incidence of transfusion ( P = 0.67), time to surgery ( P = 0.10), or length of stay ( P = 0.67). Conclusions: This study demonstrates that arthroplasty-trained surgeons perform hemiarthroplasty slightly faster than other subspecialists, but subspecialty training does not affect other perioperative outcomes, including leg length discrepancy, femoral offset, EBL, transfusion rate, time to surgery, or length of stay. This suggests that hemiarthroplasty can be adequately performed by various subspecialists, and deferring treatment to an arthroplasty surgeon might not have a clinically significant benefit in the perioperative period. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.